“Pick and choose our battles” – Understanding organizational capacity in a sport for development and peace organization - Svensson, Per G.; Hambrick, Marion E. (Sport management review, 2016)
•Practical evidence of challenges in implementing critical SDP model.•Limited ability of SDP organization to secure local community funding.•Strong perceived need for more help and addition of paid staff.•Loose organizational framework mandated by capacity constraints.•Flexibility enabled organization to manage some critical challenges. A growing number of sport for development and peace (SDP) organizations seek to address social issues through sport. Hall et al. (2003) created a multidimensional framework that suggests SDP and other nonprofit organizations need human resources, financial, and structural capacities to accomplish their organizational goals and objectives, but may face challenges with developing these capacities. The current study used this framework and examined the capacities of Gainline Africa – a small SDP nonprofit organization based in North America and operating programming in an East African post-conflict community – to identify critical elements that influenced the organization's ability to fulfill its mission. Semi-structured interviews (n=10) were conducted with its North American staff members. The study's findings build upon the theoretical understanding of organizational capacity within nonprofit sport organizations, and several new elements such as community funding and managing nontraditional Global North-Global South dynamics, were revealed that could be unique to the SDP context. Practically speaking, smaller SDP organizations can use the findings to help increase their organizational capacity through leveraging local partnerships and understanding the role and usage of paid versus volunteer staff members.